Determinants of Hypertension Self-Care Among Older Adults in Rural Central Java: A Path Analysis Study - Rosiana Eva Rayanti; Gracia Permatasari; Natalia Esti Kristanti; Aura Syafaroh; Marsela Riska Raswandaru; Ayu Afriani Panyuwa; Indrawan Adhitomo (PT.Mantaya Idea Batara, 2026)
Background: Consistent self-care is key for effective hypertension management, but is difficult for older adults in rural settings. Understanding how individual and contextual factors interact helps develop targeted nursing interventions. This study examined the determinants of self-care adherence among older adults with hypertension in rural Central Java by analyzing the direct and indirect links between hypertension knowledge, self-care profiles, and health care empowerment. Methods: A quantitative study with path analysis included 60 older adults (aged >60 years) with hypertension in Getasan District, Semarang Regency, Central Java. Data were collected from August to December 2025 via validated questionnaires and analyzed using SmartPLS and IBM SPSS version 24. Result: Health service empowerment had the strongest positive effect on self- care adherence (β = 0.402, p < 0.001). Hypertension knowledge did not directly influence adherence, but it did so through health care empowerment (β = 0.171, p = 0.004). The model explained 23% of the variance in self-care adherence (R2 = 0.230). Conclusion: Health care empowerment, rooted in patient motivation and perception, is the main factor in adherence and mediates health knowledge. Nursing interventions should shift from education to empowerment-based strategies to enhance independence in hypertension management among rural populations.